Testosterone treatment, internalizing symptoms, and body image dissatisfaction in transgender boys. (October 2021) - Grannis, Connor; Leibowitz, Scott F.; Gahn, Shane; Nahata, Leena; Morningstar, Michele; Mattson, Whitney I.; Chen, Diane; Strang, John F.; Nelson, Eric E.
Abstract: Objective: Many transgender adolescents experience clinically elevated anxiety and depression. Testosterone (T), used as a gender affirming treatment, may reduce symptoms of anxiety and depression. We assessed the effect of gender affirming T treatment on internalizing symptoms, body image dissatisfaction, and activation patterns within the amygdala-prefrontal cortex circuit in transgender adolescent boys. Method: Symptoms of generalized anxiety, social anxiety, depression, suicidality and body image dissatisfaction were measured by self-report and brain activation was measured during a face processing task with functional MRI in a group of 19 adolescent transgender boys receiving T treatment and 23 not receiving gonadal hormone treatment (UT). Results: Severity of anxiety and depression was significantly lower in the T treated group relative to the UT group, along with a trend of lower suicidality. The T group also reported less distress with body features and exhibited stronger connectivity within the amygdala-prefrontal cortex circuit compared to the UT group. Finally, group differences on depression and suicidality were directly associated with body image dissatisfaction, and anxiety symptoms were moderated by amygdala-prefrontal cortex connectivity differences between groups. Conclusion: T treatment is associated with lower levels of internalizing symptoms among transgender adolescent boys. T is also associated with greater body satisfaction and greater connectivity in a neural circuit associated with anxiety and depression. Satisfaction with body image was found to overlap with the association between T and both depression and suicidality, and amygdala-prefrontal co-activation moderated the role of T on anxiety. Highlights: Testosterone treated transgender youth have reduced internalizing symptoms. Testosterone associated with improved body image satisfaction in transgender youth. Testosterone associated with stronger amygdala-prefrontal cortex co-activation.